2012
DOI: 10.5194/bg-9-2719-2012
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the role of organic speciation in the biogeochemical cycle of dissolved cobalt in the southeastern Atlantic and the Southern Ocean

Abstract: Abstract. The organic speciation of dissolved cobalt (DCo) was investigated in the subtropical region of the southeastern Atlantic, and in the Southern Ocean in the Antarctic Circumpolar Current (ACC) and the northern Weddell Gyre, between 34°25´ S and 57°33´ S along the Greenwich Meridian during the austral summer of 2008. The organic speciation of dissolved cobalt was determined by competing ligand exchange adsorptive cathodic stripping voltammetry (CLE-AdCSV) using nioxime as a competing ligand. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…This would indicate that basalt dissolution rates are elementspecific and that Co dissolution could be slower than Fe dissolution, which can partially explain why DCo concentrations do not display their highest values close to C01, suspected to be the most impacted station by the lithogenic inputs from Heard Island for Fe, REE and Ra (Blain et al, 2008b;van Beek et al, 2008;Zhang et al, 2008;Chever et al, 2010). In addition, the organic complexation of DCo may enhance both the basaltic dissolution (Hausrath et al, 2009) and the stabilization of Co in the dissolved phase as previously observed in the Southern Ocean (Bown et al, 2012). Furthermore, the biological removal term could be much higher for Fe than for Co above the plateau, as suggested by the absence of a nutrient-like vertical distribution of DCo (Figs.…”
Section: Evidence Of a Lithogenic Source In The Vicinity Of Heard Islandmentioning
confidence: 65%
See 2 more Smart Citations
“…This would indicate that basalt dissolution rates are elementspecific and that Co dissolution could be slower than Fe dissolution, which can partially explain why DCo concentrations do not display their highest values close to C01, suspected to be the most impacted station by the lithogenic inputs from Heard Island for Fe, REE and Ra (Blain et al, 2008b;van Beek et al, 2008;Zhang et al, 2008;Chever et al, 2010). In addition, the organic complexation of DCo may enhance both the basaltic dissolution (Hausrath et al, 2009) and the stabilization of Co in the dissolved phase as previously observed in the Southern Ocean (Bown et al, 2012). Furthermore, the biological removal term could be much higher for Fe than for Co above the plateau, as suggested by the absence of a nutrient-like vertical distribution of DCo (Figs.…”
Section: Evidence Of a Lithogenic Source In The Vicinity Of Heard Islandmentioning
confidence: 65%
“…The latter study also showed that the organic complexation of DCo would probably promote Co stabilization and its transport from continental margins to the open ocean (Bown et al, 2012). According to the budget at station A08, vertical diffusion from the sediment (4.41-31.1 nmol m −2 d −1 , Fig.…”
Section: Dissolved Co Enrichment Above the Eastern Slope Of The Plateaumentioning
confidence: 99%
See 1 more Smart Citation
“…Copper and zinc complexation with HStype ligands in seawater is strong (Yang and van den Berg, 2009), and copper and iron compete for L 2 type ligands in estuarine and coastal waters (Abualhaija et al, 2015). The conditional stability constants for marine organic ligands with nickel and cobalt are high (Martino et al, 2004;Ellwood et al, 2005;Bown et al, 2012;Baars and Croot, 2015) suggesting a possible competition with iron providing they bind with the same ligands. Indeed, Cu and Ni competition for binding to the same organic ligand has been recently observed (Boiteau et al, 2016b; this issue).…”
Section: Implications Of the Co-existence Of Iron-binding Ligandsmentioning
confidence: 99%
“…This strong dependence of cellular cobalt quotas on Co' indicates that cobalt transport is not easily saturated at Co' concentrations below 16 pM, which are higher than that found in most oceanic settings (Bown et al, 2012b; Prochlorococcus iron quotas exhibited a more complex response to iron limitation. As with cobalt, lower dissolved Fe decreased both cellular Fe quotas and growth rates (Fig.…”
Section: The Relationship Betweenmentioning
confidence: 95%